Prioritization of Wind Energy Data with Analytical Hierarchy Process (AHP) - Sakon Klongboonjit; Tossapol Kiatcharoenpol (My University, 2021)
Wind energy potential is the main data to making decision for green energy projects in resident areas.The decision makers generally prioritize wind energy of alternative areas with data of wind power that are hard collected.In this study, the AHP method is introduced to prioritize wind energy of alternative areas with data of average wind velocity generally receiving from the secondary data sources.With the example of 13 alternative areas in the south of Thailand, the data of average wind velocity can be used to construct the AHP pairwise comparison matrix.Finally, the priority values of these 13 alternative areas are calculated with C.R. = 0.1157 and the wind energy priority of alternative areas is prioritized.The priority results with the data of average wind velocity are really similar to the priority results with the data of wind power.
Keywords: Prioritization; Energy Load and Power Forecasting